Survival benefit of thermal ablation therapy for patients with stage II-III non-small cell lung cancer: A propensity-matched analysis - Yang, Wei-Yu; He, Yu; Hu, Qikang; Peng, Muyun; Zhang, Zhe; Xie, Shouzhi; Yu, Fenglei (Frontiers in Oncology, 2022)
Background Thermal ablation (TA) has been considered a safe alternative therapeutic modality to surgical resection for non-small cell lung cancer (NSCLC). Previous studies have shown that TA is beneficial for stage I NSCLC patients. However, few studies have been reported on TA efficacy in patients with stage II-III NSCLC. This study aimed to investigate the influence of TA on overall survival (OS) and cancer-specific survival (CSS) in patients with stage II-III NSCLC. Methods Stage II-III NSCLC patients who did not undergo surgical resection between 2004 and 2015 were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. Propensity score matching (PSM), Kaplan–Meier survival curves, and Cox regression model were used for statistical analyses. Results A total of 57,959 stage II-III NSCLC patients who did not undergo surgical resection were included in this study, and 261 cases received TA. Overall, TA was associated with better OS (p = 0.035) and CSS (p = 0.005) than non-ablation. After 1:3 PSM, 252 patients receiving TA and 732 patients without ablation were enrolled in the matched cohort. The OS (p = 0.047) and CSS (p = 0.029) were still better in the TA group than in the non-ablation group after PSM. Cox regression analysis showed that age, sex, primary tumor site, pathological type, tumor size, radiotherapy, chemotherapy, and thermal ablation were independently associated with OS and CSS (p < 0.05). Subgroup analysis revealed that the advantages of TA were more pronounced in individuals aged ≥70 years, with tumor size ≤3.0 cm or without radiotherapy. Conclusion TA could be an effective alternative treatment for stage II-III NSCLC patients unsuitable for surgical resection, particularly those aged ≥70 years, with tumor size ≤3.0 cm or without radiotherapy.